2010
DOI: 10.1002/ceat.201000083
|View full text |Cite
|
Sign up to set email alerts
|

Production of Xylenes from Toluene and 1,2,4‐Trimethylbenzene over ZSM‐5 and Mordenite Catalysts in a Fluidized‐Bed Reactor

Abstract: The production of various xylenes from toluene, heavy aromatics such as 1,2,4-trimethylbenzene (1,2,4-TMB) and their mixture was investigated over H-ZSM-5 (H-Z), H-mordenite (H-M) and a dual zeolitic catalyst comprising ZSM-5 and mordenite (H-ZM). The experiments were conducted in a riser-simulator reactor under different operating conditions to study the effect of temperature, reaction time and feed composition on conversion and product yields. At 400°C, the conversion of toluene over the three catalysts yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The production of xylenes through disproportionation of toluene as well as transalkylation of heavy reformates (containing >80% C9 aromatics), with or without toluene or benzene, allows refineries to increase the value of the heavy reformate 1 after the clean air act banned its use as additive to gasoline because of environmental regulations. The main applications of xylenes are in the production of synthetic fibers and plasticizers, as solvents, and for gasoline blending.…”
Section: Introductionmentioning
confidence: 99%
“…The production of xylenes through disproportionation of toluene as well as transalkylation of heavy reformates (containing >80% C9 aromatics), with or without toluene or benzene, allows refineries to increase the value of the heavy reformate 1 after the clean air act banned its use as additive to gasoline because of environmental regulations. The main applications of xylenes are in the production of synthetic fibers and plasticizers, as solvents, and for gasoline blending.…”
Section: Introductionmentioning
confidence: 99%
“…Xylenes (p-, mand o-) have the greatest market demand with an increasing annual rate of 5-6% [1]. The availability of surplus toluene and low value of C 9 aromatics makes the transalkylation process an attractive method of making higher value aromatic compounds, principally xylenes [2][3][4]. Large-pore threedimensional zeolites were shown to be an active catalyst for the transalkylation process [5].…”
Section: Introductionmentioning
confidence: 99%
“…6 A number of commercial transalkylation processes have been developed such as the Xylene-Plus process developed by ARCO-IFP, 7 the Tatoray process developed by UOP, 8 and the TransPlus process developed by Mobil-CPC 9 with key operating parameters listed in Table 1. Research on transalkylation has been carried out using various types of zeolites, including both medium pore zeolites, such as ZSM-5, 10 NU-87, 11 and MCM-22, 12 and large pore zeolites, such as zeolite Y, 13 Beta, 14 mordenite, 15 SAPO-5, 16 and ZSM-12. 17 This research demonstrated that zeolite based catalysts have unique properties promoting their use in aromatic transformations.…”
Section: Introductionmentioning
confidence: 99%